Effects of Aquatic Exercise on Upper Extremity Function and Postural Control During Reaching in Children With Cerebral Palsy - Yongjin Jeon; Hye-Seon Jeon; Chunghwi Yi; Ohyun Kwon; Heonseock Cynn; Duckwon Oh (Korean Research Society of Physical Therapy, 2023)
Background: Despite the fact that aquatic exercise is one of the most popular alternative treatment methods for children with cerebral palsy (CP), there are few research regarding its effectiveness. Objects: The purpose of this study was to examine the effects of aquatic exercise on upper extremity function and postural control during reaching in children with CP. Methods: Ten participants (eight males and two females; 4-10 years; Gross Motor Function Classification System levels II-IV) with spastic diplegia were recruited to this study. The aquatic exercise program consisted of four modified movements that were selected from the Halliwick 10-point program to enhance upper extremity and trunk movements. The participants attended treatment two times a week for 6 weeks, averaging 35 minutes each session. The Box and Block Test (BBT), transferring pennies in the Bruininks-Oseretsky Test (BOT), and pediatric reaching test (PRT) scores were used as clinical measures. Three-dimensional motion analysis system was used to collect and analyze kinematic data. Differences in BBT and BOT values among pre-treatment, post-treatment, and retention (after 3 weeks) were analyzed using a Friedman test. In addition, the PRT scores and variables (movement time, hand velocity, straightness ratio, and number of movement units) from the three-dimensional motion analysis were tested using a Wilcoxon signed-rank test. The significance level was established at p < 0.05. When the results appeared to be statistically significant, a post-hoc test for multiple comparisons was performed with the Wilcoxon signed-rank test. Results: All clinical measures, which included BBT, transferring pennies of BOT, and PRT, were significantly increased between pre-intervention and post-intervention scores and between pre-intervention and retention scores after treatment (p = 0.001). Three-dimensional motion analysis mostly were significantly improved after treatment (p = 0.001). Conclusion: Aquatic exercise may help to improve body function, activity, and participation in children with varying types of physical disabilities.